PEMANFAATAN TUMBUHAN OBAT OLEH MASYARAKAT DI DESA ENTOGONG KECAMATAN KAYAN HULU KABUPATEN SINTANG - Yudas, .; Diba, Farah; Tavita, Gusti Eva (Universitas Tanjungpura, 2017)
Borneo is famous for its biodiversity richness and wealth of knowledge of traditional medicine from herbs. Knowledge passed down orally from generation to generation in the communities in Kalimantan. However, this knowledge is not documented. Therefore the research aimed to inventory the traditional knowledge of community Dayak Kebahan ethnis in Entogong village, Kayan Hulu district, Sintang Regency on used medicinal plant from the forest. This research has benefit to conservation the knowledge on utilization the traditional medicine from the forest and to conservation the medicinal plant from extinction due to the exploitation and excessive land conversion. The methods used in-depth interview and total respondents was 75 people. Result of the research showed that 71 plants have been used as traditional medicine, such as Physalis peruviana, Tinos pora rumphii, Cyathula prostrate, Imperata cylindrical, Bambusa Sp, Arhangelisia flava, Tithonia diversifolia, Euginia polyanthum, Scoparia dulcis, Hibikus mutabilis, Impatieng balsamina, Cordyline terminalis, Molineria latifolia, Selaginella doederleini, Cassiana alata, Selaginella doederleini, Urena lobata, Psidium guajava, Acorus calamus, Curcuma longa, Vitex pubescens, Morinda citrifolia, Carica papaya, Curcuma xanthorrhiza. Habitus of plants consists of liana, herb, understorey, shrub, and tree. The part of the plant used consists of root, bark, leaf, wood, flowers and seed. Family Zingiberaceae was the dominant plants used as medicine, follow by family Manispermaceae, Amaranthaceae, Asteraceae, Arecaceae, Fabaceae, Piperaceae, and Solanaceae. The plants used to overcome various diseases such as fever, skin diseases, malaria, broken bones, diarrhea, ulcers, snake bites, dengue fever, typhoid and skin burns. Methods for treatment the disease consist of drunk, taped, rubbed, sprayed, sorted, washed, and swallowed (directly). The forest in Entogong village needs to conserve due to the richness biodiversity of medicinal plant used to overcoe the disease by the community. Keywords: Entogong village, medicinal plant, Sintang Regency, traditional knowledge, West Kalimantan